Proceedings of IncoME-V & CEPE Net-2020 condition monitoring, plant maintenance and reliability, Zhuhai, China, October 23-25, 2020 - Zhen, Dong; Wang, Dong; Wang, Tianyang; Wang, Hongjun; Huang, Baoshan; Sinha, Jyoti K.; Ball, Andrew David (Mechanisms and Machine Science, 2021)
This volume gathers the latest advances, innovations and applications in the field of condition monitoring, plant maintenance and reliability, as presented by leading international researchers and engineers at the 5th International Conference on Maintenance Engineering and the 2020 Annual Conference of the Centre for Efficiency and Performance Engineering Network (IncoME-V & CEPE Net-2020), held in Zhuhai, China on October 23-25, 2020. Topics include vibro-acoustics monitoring, condition-based maintenance, sensing and instrumentation, machine health monitoring, maintenance auditing and organization, non-destructive testing, reliability, asset management, condition monitoring, life-cycle cost optimisation, prognostics and health management, maintenance performance measurement, manufacturing process monitoring, and robot-based monitoring and diagnostics. The contributions, which were selected through a rigorous international peer-review process, share exciting ideas that will spur novel research directions and foster new multidisciplinary collaborations.